USING THE AWaRe CLASSIFICATION FOR ASSESSING COMPLIANCE WITH OUTPATIENT ANTIMICROBIAL THERAPY OF CHILDREN - Khaitovych, M.V.; Temirova, O.A.; Kyrilchuk, K.Yu.; Sova, V.A.; Turchak, D.V. (World of Medicine and Biology, 2024)
In ambulatory care for children, excessive use of antibiotics is a common phenomenon, which indicates the importance of introducing antimicrobial drug administration programs into ambulatory practice. The purpose of the study was to establish the appropriateness of the choice of antimicrobial drugs in the outpatient treatment of children according to the AWaRe classification. A retrospective analysis of the antimicrobial therapy regimens of 30 consecutive children in outpatient settings was performed. It was found that 2nd (cefuroxime) and 3rd generation (cefpodoxime and cefixime) cephalosporin drugs were mainly prescribed (56.7 %), quite often (3 children each) aminopenicillins, sulfonamides, and nitrofurans were prescribed, 1 patient each received macrolide azithromycin, fluoroquinolone ofloxacin, tetracycline antibiotic doxycycline, lincosamide clindamycin. The presence of bacterial infection justified all prescriptions of antimicrobial drugs and was according to current clinical guidelines. Among the prescribed antimicrobial drugs, 19 (cephalosporins, fluoroquinolones, macrolides) belonged to the Watch group, and the others to the Access group. Therefore, in 63.3 % of cases, children in outpatient settings were prescribed drugs of the Watch group. This can contribute to the spread of antimicrobial resistance and indicates the requirement for outpatient administration of antimicrobial drugs.